Adipocytes-induced ANGPTL4/KLF4 axis drives glycolysis and metastasis in triple-negative breast cancer - Dou Yin; Nana Fang; Yaling Zhu; Xiaoqing Bao; Juan Yang; Qingyu Zhang; Ruimeng Wang; Jiahui Huang; Qibing Wu; Fang Ma; Xiaohui Wei (Journal of Experimental & Clinical Cancer Research)
Abstract Background The adipocyte-rich tumor microenvironment (TME) is recognized as a key factor in promoting cancer progression. A distinct characteristic of peritumoral adipocytes is their reduced lipid content and the acquisition of a proinflammatory phenotype. However, the underlying mechanisms by which adipocytes rewire metabolism and boost tumor progression in triple-negative breast cancer (TNBC) remain poorly understood. Methods We utilized transcriptomic analysis, bioinformatic analysis, metabolic flux analysis, protein-protein docking, gene and protein expression profiling, in vivo metastasis analysis and breast cancer specimens to explore how adipocytes reprogram tumor metabolism and progression in TNBC. Results Our findings reveal that Angiopoietin-like 4 (ANGPTL4) exhibits significantly higher expression levels in adipocyte-rich tumor circumstance compared to the symbiotic environment lacking of adipocyte. Furthermore, ANGPTL4 expression in tumor cells is essential for adipocyte-driven glycolysis and metastasis. Interleukin 6 (IL-6), enriched in cancer-associated adipocytes, and lipolysis-derived free fatty acids (FFAs) released from adipocytes, amplify ANGPTL4-mediated glycolysis and metastasis through activation of STAT3 and PPARα pathways in TNBC cells. Additionally, ANGPTL4 interacts with transcription factor KLF4 and enhances KLF4 activity, which further drives glycolysis and metastasis, whereas KLF4 knockdown attenuates migration and glycolysis in TNBC cells. Importantly, Elevated ANGPTL4 and KLF4 expression was observed in metastatic breast cancer specimens compared to non-metastatic cases and was positively correlated with poor prognosis. Conclusion Collectively, our results uncover a complex metabolic interaction between adipocytes and TNBC cells that promotes tumor aggressiveness. ANGPTL4 emerges as a key mediator in this process, making it a promising therapeutic target to inhibit TNBC progression.